Enhancing Non-Communicable Disease Management in Elderly Families: A Community Outreach Initiative - Muflih; Suwarsi; Asmarani, Fajarina Lathu; Erwanto, Rizky; Amigo, Thomas Aquino Erinyuare (Journal of Rural Community Nursing Practice, 2024)
Non-communicable diseases (NCDs) are a significant public health concern, particularly among elderly families. Limited access to healthcare resources and inadequate disease management exacerbation the impact of NCDs on this vulnerable population. This study aimed to implement a community outreach initiative focused on enhancing non-communicable disease management in elderly families. A comprehensive intervention was designed, including health education workshops, individualized health assessments, and the establishment of support networks. Pre- and post-intervention assessments were conducted to measure changes in knowledge levels, health status, health management practices, health behaviors, and family resilience among elderly families. Following the intervention, there was a substantial improvement in knowledge regarding NCDs and their management. Additionally, participants exhibited enhanced health status and more effective health management practices. Positive changes in health behaviors, such as regular exercise and balanced nutrition, were also observed. Moreover, family resilience significantly increased, strengthening their ability to cope with health challenges. The community outreach initiative demonstrated significant positive outcomes in non-communicable disease management among elderly families. Targeted interventions can play a role in empowering this demographic, improve their health and well-being, and encouraging community-based health services.